In vivo corneal confocal microscopy as a novel non‐invasive tool to investigate cardiac autonomic neuropathy in Type 1 diabetes2. Issue 2 (24th September 2014) - Maddaloni, E.; Sabatino, F.; Del Toro, R.; Crugliano, S.; Grande, S.; Lauria Pantano, A.; Maurizi, A. R.; Palermo, A.; Bonini, S.; Pozzilli, P.; Manfrini, S.
Abstract Aims To investigate whether small nerve fibre degeneration detected using corneal confocal microscopy is associated with cardiac autonomic neuropathy in people with Type 1 diabetes. Methods Thirty‐six people with Type 1 diabetes and 20 age‐ and sex‐matched healthy control subjects were enrolled. Tests to determine heart rate response to deep‐breathing (expiratory‐to‐inspiratory ratio), heart rate response to lying‐to‐stand test (30:15 ratio) and blood pressure response to standing were performed to detect cardiac autonomic neuropathy. Corneal confocal microscopy was performed to assess: corneal nerve density and corneal nerve beadings; branching pattern; and nerve fibre tortuosity. Results Compared with control participants, participants with Type 1 diabetes had fewer (mean ± sd 45.4 ± 20.2 vs 92.0 ± 22.7 fibres/mm2; P < 0.001) and more tortuous corneal nerve fibres (20 participants with Type 1 diabetes vs four control participants had nerve tortuosity grade 2/3; P = 0.022) and fewer beadings (mean ± sd 15.1 ± 3.5 vs 20.6 ± 5.0; P < 0.001). Of the participants with Type 1 diabetes, 11 met the criteria for the diagnosis of cardiac autonomic neuropathy. Corneal nerve density was significantly lower in participants with cardiac autonomic neuropathy than in those without (mean ± sd 32.8 ± 16.4 vs 51.7 ± 18.9 fibres/mm2; P = 0.008). This difference remained significant after adjustment for age (P = 0.02), gender (P = 0.04), disease duration (P = 0.005), insulin requirement (P = 0.02) and neuropathy disability score (P = 0.04). Conclusion This study suggests that corneal confocal microscopy could represent a new and non‐invasive tool to investigate cardiac autonomic neuropathy in people with Type 1 diabetes. Larger studies are required to define the role of corneal confocal microscopy in the assessment of cardiac autonomic neuropathy.